Gender at the front - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Special Paper in the CTA Annual Report 1999 presents 'The Economic Role of Women in Agricultural and Rural Development: The Promotion of Income-generating Activities'. Written by Grace Akello and Fatou Sarr